Development of occupational health culture scale: A study based on miners and construction workers - Yang, Xuesong; Zhao, Xu; Wang, Yuhao; Tong, Ruipeng (Frontiers in Public Health, 2022)
Culture is an essential influence on effectiveness of workplace health promotion, which can promote occupational health protection behavior. The aim of this research was to develop and validate an occupational health culture scale available to Chinese workers. Occupational health culture scale (OHCS) was developed based on elements of health culture and safety culture in workplace. Nine techniques steps of scale development were used, including a 15-member expert group, 10 workers for cognitive interview, and 1,119 questionnaires (from 710 miners and 409 construction workers) for formal investigation. Welch's variance analysis, independent samples t-test, Kruskal-Wallis test, Spearman correlation analysis was employed respectively to verified 9 hypotheses about impact relationship on OHCS score. After the analysis reliability and validity, the final scale consisted of 21 items in 5 domains: leadership support, coworkers support, values, policy and norms, employee involvement, physical environment. Moreover, respirable dust concentration from individual sampler had the largest negative correlation coefficient on OHCS score, -0.469 (p<0.01). The development of an occupational health culture among Chinese workers is necessary for the sustainability of human resources and the implementation of corporate responsibility.